Glossary of key concepts and terms provided by the Іnternational association for the study of pain - Golovenko, M; Voloshchuk, N (Pain medicine, 2023)
The publication collects and systematizes the main definitions and concepts related to pain sensations of various genesis and their changes in pathological conditions. The work includes terminology with appropriate changes and notes, which was prepared by the working group of the International Association for the Study of Pain (IASP) and is used in numerous reports and scientific publications. The glossary deals mainly with terms and does not contain the classification of pain, which is sufficiently presented in other modern scientific publications. The presented terms and their interpretation will be useful not only to scientists, but also to clinicians and students of medical universities of Ukraine.